Advances in mineral flotation (LACCEI, 2024)
The research study focused on the advancement of mineral flotation. This topic has gained great importance in the mining industry since it allows the recovery of the mineral, thus increasing production and profitability. The purpose of this study is to analyze, detail and publish the development of mineral flotation. The methodology is to carry out an analysis of bibliographic reviews of scientific articles taken from the Scopus database, ScienceDirect, theses, posters, etc. Reviewed bibliography of the article Innovations in mineral fleet systems have grown rapidly in recent decades, such as froth flotation, columnar flotation cells, fine and coarse particle flotation, and nanobubble flotation. It was concluded that the development of mineral flotation is very important because it has a positive effect on the profitability of the process, since it allows obtaining a high percentage of minerals.